Infrared and Terahertz Compatible Absorber Based on Multilayer Film - Yang, Mingyang; Zhou, Ming; Yu, Jianwen; Zhang, Yibo; Xu, Benyan; Cheng, Wenjun; Li, Xuyin (Frontiers in Physics, 2021)
In this paper, a similar Fabry-Perot cavity structure utilizing a multilayer film structure consisting of an ultrathin metal film is demonstrated for absorbing the infrared ray. This structure has low emissivity in the atmospheric window (3–5 and 8–14 μm) and high emissivity in the nonatmospheric window (5–8 μm). These properties improved the stealth performance which causes the high emissivity in 5–8 μm to radiate more energy to reduce its temperature. Based on this, the periodic microstructures were added to the surface of the materials that enhanced the absorption of terahertz wave (0.1–2.7 THz). The absorber based on multilayer film has a simple structure and low manufacturing cost. This work may provide a new strategy for infrared and terahertz compatible stealth technology.